The Formulation of Strategic Management for Market Development and Competition of Ground Coffee Product in SMEs of East Manggarai Regency - Awuk, Melania; Djoko Koestiono; Silvana Maulidah; Riskina Aulawiah (HABITAT, 2022)
The business unit's development is determined by its ability to design a marketing strategy. This study was intended to determine the criteria and sub-criteria for marketing resources using the ANP model and formulate an alternative marketing strategy using the TOPSIS method in small and medium enterprises (SMEs) for the ground coffee product in East Manggarai Regency. The sampling method used in this research is proposive sampling. Data collected using a questionnaire from 36 respondents. Research method study used analytical network process (ANP) and techinique for order preference by similarity to an ideal solution (TOPSIS) for the method. The ANP was used to analyze the priority of the sub-criteria of marketing resources, while the TOPSIS was used to determine the highest preference value on alternative marketing strategies. This study revealed that the sub-criteria with the highest weight for formulating alternative marketing strategies was the sub-criteria for the process of developing effective new products and services with a weight of 0.118. The highest preference value for alternative marketing strategies is the differentiation strategy with a value of 1.00. Hence, it can be concluded that an appropriate strategy for marketing development and competition of ground coffee products in SMEs of East Manggarai Regency is a differentiation strategy supported by the selected sub-criteria of the process of developing effective new products and services.